2018
DOI: 10.14495/jsiaml.10.49
|View full text |Cite
|
Sign up to set email alerts
|

A simple and fast numerical method for solving flame/smoldering evolution equations

Abstract: We propose a simple and fast numerical method for solving an evolution equation for closed flame/smoldering fronts, equivalent to the Kuramoto-Sivashinsky equation in a scale. Comparison of numerical results and an experiment suggests that our model equation is valid for not only propagating gas-phase flame fronts but also expanding smoldering fronts over thin solids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 6 publications
(10 reference statements)
0
12
0
Order By: Relevance
“…Goto et al [5] proposed a fast and simple numerical method for front tracking of (2) and reported that (2) is valid not only for propagating gaseous-flame fronts, but also for expanding smoldering fronts over thin solids.…”
Section: Introductionmentioning
confidence: 99%
“…Goto et al [5] proposed a fast and simple numerical method for front tracking of (2) and reported that (2) is valid not only for propagating gaseous-flame fronts, but also for expanding smoldering fronts over thin solids.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of this section is to define in a discrete sense the "curvature" κ and its second "derivative" κ ss arising in (6) and (7). We use a similar way of space discretization and computation of the tangential velocity to [4]. In the direct approach, a moving Jordan curve Γ(t) is approximated by a moving Jordan polygonal curve, say P(t) at time t, with N vertices labeled…”
Section: Image Segmentation By a Step-function Adjusted Method As Shmentioning
confidence: 99%
“…and ω is a sufficiently large constant. Then, r i → L/N (t → ∞) is satisfied (see [4,8,9,11] in detail). From the above, (10) can be summarized as the following ODEs:…”
Section: Image Segmentation By a Step-function Adjusted Method As Shmentioning
confidence: 99%
See 2 more Smart Citations